Evaluating the effectiveness of 360 videos when teaching primary school subjects related to environmental education - Emmanuel Fokides; Paraskevi Anna Arvaniti (Journal of Pedagogical Research, 2020)
The study presents the results of a project in which 360° videos were used for informing students about subjects related to environmental education. The target group was forty-four, nine- to ten-year-old students, who used three teaching tools, namely printed material, web pages, and 360° videos. The project lasted for twelve two-teaching-hour sessions (four for each tool), and data were collected by means of evaluation sheets and a questionnaire for recording their views and attitudes. It was found that the 360° videos yielded better learning outcomes compared to the other tools. The sense of presence was also greater in this tool. Then again, all tools were considered as equally motivating and effective. Moreover, the 360° videos were considered more enjoyable and easier to use only when compared to the printed material. Though the findings confirmed that 360° videos can be effective in raising students' awareness of environmental problems, they also point to the need of finding innovative methods and teaching frameworks that would allow educators to fully exploit their educational potential.